2013
DOI: 10.1111/aphw.12013
|View full text |Cite
|
Sign up to set email alerts
|

Changing Outcome Expectancies, Drinking Intentions, and Implicit Attitudes toward Alcohol: A Comparison of Positive Expectancy‐Related and Health‐Related Alcohol Warning Labels

Abstract: This first test of warning labels that contradict positive alcohol outcome expectancies provided promising results; thus warning labels could be considered as means to influence college-aged people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 58 publications
3
36
0
3
Order By: Relevance
“…Moreover, warning labels contradicting positive outcome expectancies lowered drinking intentions and the perception of positive alcohol-related outcome expectancies [47]. In line with this research, there is also a first support for the effectiveness of contradicting positive smoking outcome expectancies [48].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, warning labels contradicting positive outcome expectancies lowered drinking intentions and the perception of positive alcohol-related outcome expectancies [47]. In line with this research, there is also a first support for the effectiveness of contradicting positive smoking outcome expectancies [48].…”
Section: Introductionsupporting
confidence: 77%
“…A recent study has shown that warning labels contracting positive alcohol-related outcomes expectancies have changed implicit attitudes toward alcohol into more negative ones [47], while warning labels focusing on health-damaging aspect of alcohol consumption resulted in more positive implicit attitudes [47]. Moreover, warning labels contradicting positive outcome expectancies lowered drinking intentions and the perception of positive alcohol-related outcome expectancies [47].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol warning labels are intended to increase knowledge and attitudes regarding the harmful consequences of alcohol use and promote changes in consumption behaviour [20]. Although there is no substantial evidence in the literature on the effectiveness of alcohol warning labels in changing behaviour, especially among groups at risk [22,23,24,46], previous research revealed that this could be due to narrow implementation, to the generic nature of the messages used, and to their poor visibility [21,22,28,46]. In this regard, in order to increase the likelihood of alcohol warning messages being perceived as relevant, they need to be congruent with the beliefs of the target audience [9,28].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, while there is broad consensus that this type of information may improve knowledge and raise awareness and prompt discussion on the harmful health and social consequences of alcohol abuse [10,20], mixed results have been obtained in numerous studies examining the effectiveness of alcohol warning statements in changing consumer behaviour [22]. In particular, studies performed in the United States have found that alcohol warnings have no effect on beliefs about alcohol or intended alcohol-related behaviour [23], while others have found moderate effects on consumption [24]. According to Al-hamdani (2014) [22], the mixed results obtained in previous studies are mainly connected to the weak content of warnings on alcohol products, their poor visibility, and the lack of pictorial content.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation